2023
DOI: 10.3390/ijms24086933
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Effects of Syndecan-4 Knockdown on Skeletal Muscle Functions

Abstract: The remodelling of the extracellular matrix plays an important role in skeletal muscle development and regeneration. Syndecan-4 is a cell surface proteoglycan crucial for muscle differentiation. Syndecan-4−/− mice have been reported to be unable to regenerate following muscle damage. To investigate the consequences of the decreased expression of Syndecan-4, we have studied the in vivo and in vitro muscle performance and the excitation–contraction coupling machinery in young and aged Syndecan-4+/− (SDC4) mice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…The front-rear polarity should be maintained during migration, because this biochemical process is required to block the formation of lamellipodia at the trailing edges [46,48,49]. Here, we show that resting [Ca 2+ ] i is not significantly different in Ctrl, Scr, and KD myoblasts; however, upon activation the migrating cells have increased [Ca 2+ ] i , as it has been proven recently in C2C12 cells with a decreased expression of cell surface protein Syndecan-4 [50]. Interestingly, this elevation in [Ca 2+ ] i is significantly lower in migrating KD cells compared to that of their control counterparts, which might be related to Septin7 depletion.…”
Section: Modified Septin7 Expression Alters [Ca 2+ ] I Homeostasis In...supporting
confidence: 78%
“…The front-rear polarity should be maintained during migration, because this biochemical process is required to block the formation of lamellipodia at the trailing edges [46,48,49]. Here, we show that resting [Ca 2+ ] i is not significantly different in Ctrl, Scr, and KD myoblasts; however, upon activation the migrating cells have increased [Ca 2+ ] i , as it has been proven recently in C2C12 cells with a decreased expression of cell surface protein Syndecan-4 [50]. Interestingly, this elevation in [Ca 2+ ] i is significantly lower in migrating KD cells compared to that of their control counterparts, which might be related to Septin7 depletion.…”
Section: Modified Septin7 Expression Alters [Ca 2+ ] I Homeostasis In...supporting
confidence: 78%
“…A previous study showed that SDC4 was required to maintain the proliferation ability of skeletal muscle cells [ 18 ]. However, it is not known whether SDC4 regulates cell proliferation and migration during heart regeneration.…”
Section: Resultsmentioning
confidence: 99%
“…The syndecan family includes four members (syndecan-1, -2, -3, and -4) that are differentially expressed in various tissues and cell types ( Lambaerts et al, 2009 ; Velleman, 2012 ). Syndecans play critical roles in cell adhesion, proliferation, differentiation, migration, and survival ( Couchman et al, 2015 ) and are important for skeletal muscle growth, health, and aging ( Pisconti et al, 2012 ; Rønning et al, 2015 ; Pisconti et al, 2016 ; Velleman and Song, 2017 ; Rønning et al, 2020 ; Sztretye et al, 2023 ). They also play a role in ECM remodeling and can act as co-receptors for growth factors, chemokines, and extracellular matrix molecules ( Xian et al, 2009 ; Couchman, 2010 ; Lunde et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%